Evaluating the research performance of women scientists in Indian research laboratories based on Scopus citation database: A bibliometric analysis - Mukherjee, Bhaskar (Malaysian Journal of Library and Information Science, 2022)
This study examines the contributions of women scientists currently working in various research organizations under the Ministry of Science and Technology, India. Women scientists were identified through the official websites of the research laboratories and their publication performance has been tracked using the Scopus database. There are 901 women scientists working in 78 research organizations under the Ministry and have published 21810 publications up to December 2019, almost 65 percent of which has been appeared during 2010 to 2019. The publication per scientist has risen from 6.85 article per year before 2000 to 10.45 paper in 2015-2019 which indicates increasing participation of women in science from India. Women scientists are primarily engaged in biological sciencesresearch, however fields such as materials sciences, nano-technology, and astrophysics are also becoming the preferred subject choices among women. Women scientists mostly published their articles as a member of a team of utmost 10 authors, however, their position in multi-authored articles is mostly as co-authors than that of principal authors. Women in the age group ofbetween31 to 40 produced maximum publications, and almost 98 percent of publications appeared in collaboration with other scientists.This study confirms that publication productivity does not decline with age. There are women scientists who stay active in research and keep their productivity at a high level until their retirement. The study suggests that the increasing participation of women in Indian science is encouraging, as such more funding opportunities to younger women researchers may be important to give them more lead time to build a strong career.